The Abstract Work and the Concept of Competence: Discussing this Interrelation in the Context of Industrial Labor - Zandonade, Viviane; Bianco, Mônica de Fatima (Organizações & Sociedade, 2014)
This paper aims to discuss the application of the knowledge and notion in competence of people’s management system, questioning whether their way of administration brings back the work to the workers, valuing their knowledge. For such reason, it discusses the work as the founder of social praxis, aspects of their position in the capitalist production system and their relation with notion of competence. The applied study was conducted in a big food industry through a qualitative and documental research and interviews. It was noticed, not definitely, that the delivery process derived from this way of management can produce an individual engagement that, even overcoming the fragmentation, puts the worker far from a perception of a collective author and of been part of a social class. It can be affirmed that gives rise to a less alienated work in the process and more abstract in the social relationship.